Anchoring CoFe2O4 Nanoparticles on N‐Doped Carbon Nanofibers for High‐Performance Oxygen Evolution Reaction. Issue 11 (7th August 2017) - Li, Tongfei; Lv, Yinjie; Su, Jiahui; Wang, Yi; Yang, Qian; Zhang, Yiwei; Zhou, Jiancheng; Xu, Lin; Sun, Dongmei; Tang, Yawen
Abstract: The exploration of earth‐abundant and high‐efficiency electrocatalysts for the oxygen evolution reaction (OER) is of great significant for sustainable energy conversion and storage applications. Although spinel‐type binary transition metal oxides (AB2 O4, A, B = metal) represent a class of promising candidates for water oxidation catalysis, their intrinsically inferior electrical conductivity exert remarkably negative impacts on their electrochemical performances. Herein, we demonstrates a feasible electrospinning approach to concurrently synthesize CoFe2 O4 nanoparticles homogeneously embedded in 1D N‐doped carbon nanofibers (denoted as CoFe2 O4 @N‐CNFs). By integrating the catalytically active CoFe2 O4 nanoparticles with the N‐doped carbon nanofibers, the as‐synthesized CoFe2 O4 @N‐CNF nanohybrid manifests superior OER performance with a low overpotential, a large current density, a small Tafel slope, and long‐term durability in alkaline solution, outperforming the single component counterparts (pure CoFe2 O4 and N‐doped carbon nanofibers) and the commercial RuO2 catalyst. Impressively, the overpotential of CoFe2 O4 @N‐CNFs at the current density of 30.0 mA cm −2 negatively shifts 186 mV as compared with the commercial RuO2 catalyst and the current density of the CoFe2 O4 @N‐CNFs at 1.8 V is almost 3.4 times of that on RuO2 benchmark. The present work would open a new avenue for the exploration of cost‐effective and efficient OER electrocatalysts to substitute noble metals for various renewable energy conversion/storage applications. Abstract : A simple and scalable electrospinning strategy is developed for the concurrent synthesis of CoFe2 O4 nanoparticles homogeneously embedded in N‐doped carbon nanofibers (denoted as CoFe2 O4 @N‐CNFs). The synthesized CoFe2 O4 @N‐CNFs are demonstrated superior oxygen evolution reaction performance with a low overpotential, a large current density, a small Tafel slope, and long‐term durability in alkaline solution.